The Boolean expression

Question:

The Boolean expression

$((\mathrm{p} \wedge \mathrm{q}) \vee(\mathrm{p} \vee \sim \mathrm{q})) \wedge(\sim \mathrm{p} \wedge \sim \mathrm{q})$ is equivalent to:

 

  1. $\mathrm{p} \wedge(\sim \mathrm{q})$

  2. $p \vee(\sim q)$

  3. $(\sim p) \wedge(\sim q)$

  4. $\mathrm{p} \wedge \mathrm{q}$


Correct Option: , 3

Solution:

(3) $(\sim p) \wedge(\sim q)$

Leave a comment

Close
faculty

Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now